KEANEKARAGAMAN JENIS ANGGREK DI KAWASAN HUTAN DESA REJEKI KECAMATAN PALOLO KABUPATEN SIGI - Wololi, Januar Harun; Mallombasang, Sri Ningsih; Sustri, Sustri; Rahmawati, Rahmawati (Universitas Tadulako, 2021)
Indonesia is an archipelago located on the equator which makes Indonesia very rich in biodiversity, such as trees, epiphytes, lianas, orchids and others. Specifically for Indonesian orchids, it is estimated that there are approximately 3,000 types of orchids. But until now, certain information regarding the distribution and ecological character in particular is still very limited. The purpose of this study was to determine the diversity of orchid species found in the Forest Zone of the Rejeki Village. This research was conducted from March to May 2018, located in the Rejeki Village Forest Area, Palolo District, Sigi Regency. Orchid data collected includes types of orchids, the number of individual orchids of each type. This research was carried out exploratively in the forest area. The method used is the path method carried out by purposive sampling line (intentional) and then systematically sampling. Data were analyzed using the Type (H ') Diversity Index. The results showed that the calculation of the diversity index of orchid species (H ') in the village of Rejeki, Palolo Subdistrict, Sigi Regency, Central Sulawesi Province was classified as moderate at 1.71231. The results of the calculation of the Diversity Index (H ') for each natural orchid species found at a research location that has a high H' value are Spathoglotis plicata Blume species. With a large value of 0.36724 or 23 species out of 59 natural species found. Subsequently followed by species of Phreatia micranha (A.Rich.) Lindl) with an H value of 0.35961 or 12 species from 59 species of natural orchids, Ceologyne celebensis J. J.Sm with an H value of 0.27093 or 8 species.Kata Kunci : Keanekaragaman, Anggrek, Desa Rejeki, Kabupaten Sigi